1997
DOI: 10.1088/0264-9381/14/8/019
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions in multi-dimensional cosmology with shear and bulk viscosity

Abstract: Multidimensional cosmological model describing the evolution of a fluid with shear and bulk viscosity in n Ricci-flat spaces is investigated. The barotropic equation of state for the density and the pressure in each space is assumed. The second equation of state is chosen in the form when the bulk and the shear viscosity coefficients are inversely proportional to the volume of the Universe. The integrability of Einstein equations reads as a colinearity constraint between vectors which are related to constant p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…From (42)- (44), it is easily seen that θ, σ 2 , 2 are constants which depend on shear viscosity coefficient. U 3 are functions of x and t for two cases.…”
Section: Conclusion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…From (42)- (44), it is easily seen that θ, σ 2 , 2 are constants which depend on shear viscosity coefficient. U 3 are functions of x and t for two cases.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Pradhan et al [42] have presented some inhomogeneous magnetized viscous fluid cosmological models with varying in Bianchi type universe. The model with shear and bulk viscosity were investigated by Elst [43] and Gavrilov [44]. Furthermore, the matter distribution is not expected to attain thermal equilibrium in the early stages, it is understandable that there would be heat flux in the universe [45].…”
mentioning
confidence: 99%
“…He deduced that viscosity plays an important role in the process of isotropization of the universe. Models with both the bulk and shear viscosity were obtained by Gavrilov et al (1997). Krori and Mukherjee (2000) studied the effect of bulk viscosity in the evolution of anisotropic Bianchi-I models.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand Belinskii and Khalatnikov [7] have studied the nature of cosmological solutions of a homogeneous Bianchi type-I model by taking into account the dissipative process due to viscosity and showed that viscosity can not remove the initial big bang singularity rather it can cause qualitatively new behavior of the solutions near the singularity. Banerjee et al [8,9], Barrow [10], Grøn [11], Gavrilov et al [12], Arbab [13], Beesham et al [14], Krori and Mukherjee [15] and many others have studied viscous cosmological models in different contexts. Grøn [11] has reviewed viscous cosmological models and deduced that viscosity plays an important role in the process of isotropization of the universe.…”
Section: Introductionmentioning
confidence: 99%